Marketing strategy of Japan Airlines between Kuala Lumpur and Kansai sector / Shaidatul Nuraheem Abdul Rashid - Abdul Rashid, Shaidatul Nuraheem (Faculty of Business and Management, 1995)
JAL ( Japan Airlines ) has been regarded as one of the most successful airline in the world. Functioning; also as the national carrier, JAL provide services to other parts of the world and covering services to most airport in Japan. Due to the restraint of night operations and congestion that occurs at most of the airports in Japan, die Kansai International Airport was then build and opened to the world on September 4th, 1994. However, since JAL started it's service between Kuala Lumpur and Kansai, JAL has been experiencing low load factor on the Kuala Lumpur to Kansai sector. There were many factors that contributed to the decline of passenger load and one of die main factor is due to the lack of marketing effort done by JAL…